InvestiGators. Braver and boulder - Green, John Patrick, 1975- (Green, John Patrick, 1975- InvestiGators (Series), 2022)
The InvestiGators are having a hard time keeping a low profile with their new headquarters being a giant robot towering over the city! How can they be SECRET agents if everyone recognizes them? But with their ears to the ground, Mango and Brash hear mysterious rumblings about BOULDER BUDDIES ... are they just the latest fad or part of a mob-run scheme? And could a rocky relationship from the InvestiGators' past be trembling beneath the surface? Find out in their most stone-cold dangerous mission yet!